APT Detection via Hypergraph Attention Network with Community-Based Behavioral Mining - Qijie Song; Tieming Chen; Tiantian Zhu; Mingqi Lv; Xuebo Qiu; Zhiling Zhu (Applied Sciences)
Advanced Persistent Threats (APTs) challenge cybersecurity due to their stealthy, multi-stage nature. For the provenance graph based on fine-grained kernel logs, existing methods have difficulty distinguishing behavior boundaries and handling complex multi-entity dependencies, which exhibit high false positives in dynamic environments. To address this, we propose a Hypergraph Attention Network framework for APT detection. First, we employ anomaly node detection on provenance graphs constructed from kernel logs to select seed nodes, which serve as starting points for discovering overlapping behavioral communities via node aggregation. These communities are then encoded as hyperedges to construct a hypergraph that captures high-order interactions. By integrating hypergraph structural semantics with nodes and hyperedge dual attention mechanisms, our framework achieves robust APT detection by modeling complex behavioral dependencies. Experiments on DARPA and Unicorn show superior performance: 97.73% accuracy, 98.35% F1-score, and a 0.12% FPR. By bridging hypergraph theory and adaptive attention, the framework effectively models complex attack semantics, offering a robust solution for real-time APT detection.